Impact of educational session on knowledge and attitude towards teratogenicity among undergraduate medical students: a comparative study - Kumari, Priyanka; Krishnaiah, Vasundara; Kumaraswamy, Girish; Tamboli, Tushar J. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Teratogenicity is a major cause of abortion, still birth and can result in longterm disability with a significant impact on individuals, families, societies and healthcare systems. Drugs being one of the causes of teratogenicity, creating awareness among medical students, the future prescribing physicians, the rate of teratogenicity can be decreased. The objective was to compare the attitude and knowledge about teratogenicity among the medical undergraduates before and after an educational session on teratogenicity. Methods: A pre-validated semi structured questionnaire on attitude and knowledge about teratogenicity was distributed to 2nd year medical students (147) before and after teratogenicity educational session. Results obtained were compared within the group. Paired t test was used for within the group comparison. P-Value <0.05 was considered to be statistically significant. Results: Improvement in knowledge showed statistically significant improvement following teratogenicity educational session (P-Value=0.0003). Improvement was there in post session attitude scores as well, however, it was not significant (P-Value=0.64). Conclusions: Early reinforcement about teratogenicity in medical students enables them to decide appropriate drug therapy while prescribing for females of reproductive age group.